Informacijska varnost in organizacije - Prislan, Kaja; Bernik, Igor (University of Maribor Press, 2019)
Information security and organizations. Information and cyber threats pose a high risk for organizations. They develop exponentially fast and are becoming more and more sophisticated and unpredictable. Taking into account the consequences and the damage that may be caused by information security incidents by the realization of threats, the business success of organizations depends on efficient management of information systems and information security. To reduce the security risks, organizations need to manage technological development responsibly and thoughtfully. This monograph presents the position of information security in the business environment and approaches for its effective management. We draw attention to the current management challenges by reviewing organizational practices. Based on the synthesis of good practices and standards, the most important measures for protecting information are described. These measures contribute to the quality of information systems protection, a high level of security culture and continuous business operations in organizations.